THE BOOK OF SONGS AND HEALTH CULTURE: INSIGHTS FOR MODERN LIFE - Du, Weimin; Suvimolstien, Chusak; Panthupakorn, Poradee; Kosaiyawat, Suwichai (วารสารสหวิทยาการสังคมศาสตร์และการสื่อสาร, 2026)
Introduction: Health preservation culture is an important component of traditional Chinese civilization. The Book of Songs, as the earliest anthology of Chinese poetry, records early Chinese views on nature, life, diet, labor, and emotional well-being. However, limited studies have explored its health preservation wisdom from a multidimensional perspective and its relevance to modern life. Objective: This study aims to examine the historical development of The Book of Songs, explore its embedded health preservation wisdom, and investigate its implications for contemporary lifestyles. Method: A qualitative approach was employed using qualitative content analysis. Relevant textual materials, including The Book of Songs and related studies, were analyzed to identify and interpret health-related themes. Results: The findings reveal that The Book of Songs embodies a multidimensional health preservation culture grounded in harmony with nature and longevity ideals. Key dimensions include medical health preservation, dietary therapy, residential wellness, physical activity, and emotional regulation. A Health Preservation Framework from The Book of Songs was proposed to explain these interrelated dimensions. Conclusion: The study suggests that the health wisdom in The Book of Songs remains relevant to modern healthy lifestyles and contributes to the contemporary understanding of traditional Chinese health culture.